Gain with no pain? Pain management in dermatological photodynamic therapy. (1st September 2017) - Wang, B.; Shi, L.; Zhang, Y.F.; Zhou, Q.; Zheng, J.; Szeimies, R.M.; Wang, X.L.
Summary: Pain during photodynamic therapy (PDT) is the main limiting adverse effect in its use in dermatology. Given its multifactorial nature, we reviewed both intrinsic and extrinsic factors that are involved in PDT pain. We propose a threshold theory for pain experience in PDT: it correlates positively with fluence rate and dose below a certain threshold (rate of 60 mW cm −2, dose of 50 J cm −2 ); when the threshold is surpassed, pain intensity saturates. Additionally, we carefully compared recent updates on pain management strategies and we suggest that cold‐air analgesia and low‐irradiance light sources (such as variable pulsed light and daylight PDT) represent the current best analgesic options. Finally, we discuss the possible mechanisms of pain experience during PDT. Reactive oxygen species, transient receptor potential channels and inflammatory responses are key mediators in pain. Further investigation into these pathways should help with the development of more effective analgesic strategies. Taking these points together, for pain management in PDT, an individualized plan of analgesia is possible.